Pengaruh Good Corporate Governance Dan Kinerja Keuangan Pada Harga Saham Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2009-2011 - Ramdiani, Ni Nyoman; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2013)
This study aimed to determine the relationship between good corporate governance and financial performance at the price of banking stocks listed on the Indonesia Stock Exchange in 2009-2011. Good corporate governance is proxied by the proportion of independent commissioners and the number of audit committee members. Financial performance is proxied by ROA, LDR and CAR. The data analysis technique used in this study were multiple linear regression analysis techniques. The analysis showed that the number of members of the audit committee and the ROA effect on bank stock prices, while the proportion of independent commissioners, LDR and CAR had no effect on the price of bank shares. Keywords : corporate governance, financial performance, stock prices